Low-alkali corrosion-resistant seawater and sea sand concrete with composite gel system and preparation method of low-alkali corrosion-resistant seawater and sea sand concrete
By introducing ferroalaluminate cement and carbonized regenerated micro powder into the composite gelling system, the internal alkalinity of concrete is reduced, and the problem of shortening the life of marine civil engineering structures in marine corrosion environments is solved, the service life of FRP ribs is improved and the needs of large-scale civil engineering construction are met.
Patent Information
- Application Number
- CN202510082151.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-29
AI Technical Summary
In the marine corrosion environment of high salt, high temperature, high humidity and high ultraviolet rays, problems such as steel bar corrosion and concrete cracking have led to a shortening of the life of marine civil engineering structures, and FRP ribs have the risk of mechanical properties degradation in high temperature, humidity and high alkaline environments of concrete.
The seawater and sea sand concrete is adopted with a low-alkali corrosion-resistant composite gelling system. By introducing ferroalaluminate cement and carbonized regenerated micro powder into the composite gelling system, the alkalinity of the pore solution inside the concrete is reduced and the mechanical strength and durability of the concrete are improved.
It significantly improves the service life of FRP tendons in marine environments, meets the needs of large-scale civil engineering construction, and reduces the comprehensive energy consumption and carbon emissions of the gelling system.
Smart Images

Figure BDA0005249013500000061
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a low-alkali corrosion-resistant composite cementitious system seawater and sea sand concrete and a preparation method thereof. Background Art
[0002] In the harsh marine corrosion environment of "high salt, high temperature, high humidity, and high ultraviolet rays", problems such as steel corrosion and concrete cracking have greatly shortened the service life of marine civil engineering structures, and the safety of the structure during service cannot be ignored. In addition, the direct use of marine construction materials such as seawater and sea sand will introduce a high-content chloride ion environment, accelerating the damage to the concrete structure caused by steel corrosion. Fiber-reinforced composite material FRP material has excellent chloride corrosion resistance and the characteristics of light weight and high strength. It is an ideal material to replace easily corroded steel bars in marine corrosion environments. However, FRP bars are at risk of mechanical property degradation in high temperature, humidity and high alkalinity environments of concrete. In addition, the expansion damage caused by the invasion of corrosive ions such as sulfates on concrete is also one of the main reasons for the shortened service life of marine civil engineering structures. Therefore, it is necessary to study a seawater and sea sand concrete with low-alkali corrosion resistance to improve the service life of FRP bars in marine environments.
[0003] Using the pozzolanic effect of mineral admixtures to consume calcium hydroxide, a hydration product of silicate cement, is an effective way to reduce the alkalinity of the pore solution inside concrete. However, the addition of a high proportion (>50%) of mineral admixtures will lead to poor mechanical properties of concrete, making it difficult to directly use it in large-scale civil engineering construction. Summary of the invention
[0004] In view of this, the object of the present invention is to provide a low-alkali corrosion-resistant composite cementitious system seawater sand concrete and a preparation method thereof. The seawater sand concrete provided by the present invention has the advantages of low-alkali corrosion resistance and good mechanical properties, can enhance the service life of FRP bars in marine environments, and meet the needs of large-scale civil engineering construction.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a low-alkali corrosion-resistant composite cementitious system seawater and sea sand concrete, which comprises the following raw materials in parts by mass:
[0007] 7 parts of Portland cement, 2-4 parts of ferroaluminate cement, 1.5-2.5 parts of carbonized regenerated micropowder, 20-30 parts of sea sand, 5-7 parts of sea water, 0-0.05 parts of water reducer, and 0-0.02 parts of retarder.
[0008] Preferably, the preparation of the carbonized regenerated micropowder comprises: crushing and ball-milling the waste hardened cement slurry in sequence to obtain the regenerated micropowder; and carbonizing the regenerated micropowder to obtain the carbonized regenerated micropowder.
[0009] Preferably, the carbonization conditions include: temperature of 20-30°C, relative humidity of 60-80%, air pressure of 1 atmosphere, CO 2 The volume concentration is 20% and the carbonization time is 15 to 20 days.
[0010] Preferably, the particle size of the carbonized regenerated micropowder is less than 0.075 mm.
[0011] Preferably, the silicate cement comprises PO52.5R cement.
[0012] Preferably, the strength grade of the ferroaluminate cement is 42.5.
[0013] Preferably, the particle size of the sea sand is 0.08 to 2 mm.
[0014] The present invention provides a method for preparing the low-alkali corrosion-resistant composite cementitious system seawater and sea sand concrete according to the above scheme, comprising the following steps:
[0015] The raw materials are mixed to obtain the low-alkali corrosion-resistant composite cementitious system seawater and sea sand concrete.
[0016] Preferably, the mixing comprises: first mixing silicate cement, ferroaluminate cement, carbonized regenerated micro powder and sea sand, and then adding a mixture of seawater, a water reducer and a retarder to the obtained mixture for second mixing.
[0017] Preferably, after the mixing, the obtained mixture is further subjected to molding and seawater immersion curing in sequence.
[0018] The invention provides a low-alkali corrosion-resistant composite cementitious system seawater and sea sand concrete, which comprises the following raw materials, measured by mass: 7 parts of silicate cement, 2-4 parts of ferroaluminate cement, 1.5-2.5 parts of carbonized regenerated micropowder, 20-30 parts of sea sand, 5-7 parts of seawater, 0-0.05 parts of water reducing agent, and 0-0.02 parts of retarder.
[0019] The present invention introduces ferroaluminate cement into the composite cementitious system, which can reduce the amount of silicate cement, reduce the content of calcium hydroxide produced by silicate cement hydration, and reduce the alkalinity of the pore solution inside the concrete; the introduction of ferroaluminate cement and carbonized regenerated micropowder into the composite cementitious system can improve the mechanical strength and durability of seawater and sea sand concrete of the composite cementitious system, and at the same time reduce the comprehensive energy consumption and carbon emission of the cementitious system. The phase composition of the carbonized regenerated micropowder is various crystalline and amorphous calcium carbonate and highly active silica gel, wherein calcium carbonate can promote the hydration reaction of ferroaluminate cement and improve the mechanical strength of the composite cementitious system concrete, and at the same time, high-activity silica gel can be used to replace mineral admixtures to consume calcium hydroxide produced by silicate cement hydration, thereby achieving the purpose of reducing the alkalinity of the composite cementitious system concrete.
[0020] In addition, the carbonized regenerated micropowder of the present invention is obtained by carbonizing the regenerated micropowder. The carbonization and utilization of the regenerated micropowder can, on the one hand, achieve the effect of absorbing and solidifying carbon dioxide, and on the other hand, can improve the resource utilization rate of waste building materials. DETAILED DESCRIPTION
[0021] The present invention provides a low-alkali corrosion-resistant composite cementitious system seawater and sea sand concrete, which comprises the following raw materials in parts by mass:
[0022] 7 parts of Portland cement, 2-4 parts of ferroaluminate cement, 1.5-2.5 parts of carbonized regenerated micropowder, 20-30 parts of sea sand, 5-7 parts of sea water, 0-0.05 parts of water reducer, and 0-0.02 parts of retarder.
[0023] The carbonized regenerated micropowder is first described below.
[0024] In the present invention, the preparation of the carbonized regenerated micropowder preferably comprises: crushing and ball-milling the waste hardened cement slurry in sequence to obtain the regenerated micropowder; and carbonizing the regenerated micropowder to obtain the carbonized regenerated micropowder.
[0025] In the present invention, the crushing is preferably crushed into small pieces with a particle size of less than 1 cm; the present invention has no special requirements for the conditions of the ball milling, and the particle size of the regenerated micro powder is less than 0.075 mm. In the embodiment of the present invention, the ball milling is specifically carried out at a speed of 600 r / min for 7 minutes (forward rotation for 1 minute, rest for 1 minute, reverse rotation for 1 minute, rest for 1 minute, forward rotation for 1 minute, rest for 1 minute, reverse rotation for 1 minute).
[0026] In the present invention, the carbonization conditions preferably include: a temperature of 20 to 30°C, a relative humidity of 60 to 80%, an atmospheric pressure of 1 atmosphere, and a CO 2 The volume concentration is 20% and the carbonization time is 15 to 20 days.
[0027] In an embodiment of the present invention, the carbonization temperature may be 20°C, 25°C or 30°C; the relative humidity may be 60%, 65%, 70%, 75% or 80%; and the carbonization time may be 15 days, 16 days, 17 days, 18 days, 19 days or 20 days.
[0028] In the present invention, the regenerated micropowder is preferably spread flat in a carbonization box for carbonization, and the thickness of the regenerated micropowder layer is preferably 1 to 2 mm.
[0029] In the present invention, the main components of the waste hardened cement paste are unhydrated cement particles, various hydration products and fine aggregate particles. The present invention can carbonize the calcium hydroxide and unhydrated silicate mineral phase in the regenerated micropowder into calcium carbonate through carbonization, which can avoid increasing the alkalinity of the composite gelling system after hydration on the one hand, and on the other hand, the calcium carbonate produced by carbonization promotes the hydration of the composite gelling system to obtain higher mechanical properties. In addition, the present invention carbonizes the CSH gel through carbonization to obtain calcium carbonate and active silica gel. The role of calcium carbonate is as described above, and the active silica gel can be used to consume the calcium hydroxide produced in the hydration process of the composite gelling system to achieve the purpose of reducing alkalinity.
[0030] After the carbonization is completed, the present invention preferably further comprises crushing and ball milling the obtained carbonized material again, and finally screening to obtain carbonized regenerated micro powder that meets the particle size requirements. The present invention has no special requirements for the conditions of the re-crushing and ball milling. In the present invention, the particle size of the carbonized regenerated micro powder is preferably less than 0.075 mm.
[0031] The low-alkali corrosion-resistant composite cementitious system seawater and sea sand concrete is described below.
[0032] The low-alkali corrosion-resistant composite cementitious system seawater and sea sand concrete provided by the present invention comprises 7 parts of Portland cement by weight. In the present invention, the Portland cement preferably comprises PO52.5R cement.
[0033] Based on the mass fraction of the silicate cement, the low-alkali corrosion-resistant composite cementitious system seawater sand concrete provided by the present invention includes 2 to 4 parts of ferroaluminate cement, and in a specific embodiment, it can be 2 parts, 3 parts or 4 parts. In the present invention, the strength grade of the ferroaluminate cement is preferably 42.5. The present invention introduces ferroaluminate cement into the composite cementitious system, which can reduce the amount of silicate cement, reduce the content of calcium hydroxide produced by the hydration of silicate cement, reduce the alkalinity of the pore solution inside the concrete, and thus reduce the demand for mineral admixtures for the low alkalinity target.
[0034] Based on the mass fraction of the silicate cement, the low-alkali corrosion-resistant composite cementitious system seawater sand concrete provided by the present invention includes 1.5 to 2.5 parts of carbonized regenerated micropowder, and in a specific embodiment, it can be 1.5 parts, 2 parts or 2.5 parts. In the present invention, the phase composition of the carbonized regenerated micropowder is various crystalline and amorphous calcium carbonate and highly active silica gel, wherein calcium carbonate can promote the hydration reaction of ferroaluminate cement and improve the mechanical strength of the composite cementitious system concrete. At the same time, high-activity silica gel can be used to replace mineral admixtures to consume calcium hydroxide produced by silicate cement hydration, thereby achieving the purpose of reducing the alkalinity of the composite cementitious system concrete.
[0035] Based on the mass fraction of the silicate cement, the low-alkali corrosion-resistant composite cementitious system seawater sand concrete provided by the present invention includes 20 to 30 parts of sea sand, and in a specific embodiment, it can be 20 parts, 22 parts, 24 parts, 26 parts, 28 parts or 30 parts. In the present invention, the particle size of the sea sand is preferably 0.08 to 2 mm.
[0036] Based on the mass fraction of the silicate cement, the low-alkali corrosion-resistant composite cementitious system seawater and sea sand concrete provided by the present invention includes 5 to 7 parts of seawater, and in a specific embodiment, it can be 5 parts, 6 parts or 7 parts.
[0037] Based on the mass fraction of the silicate cement, the low-alkali corrosion-resistant composite cementitious system seawater and sea sand concrete provided by the present invention includes 0 to 0.05 parts of a water reducer, and in a specific embodiment, it can be 0 parts, 0.01 parts, 0.02 parts, 0.03 parts, 0.04 parts or 0.05 parts. The present invention has no special requirements for the specific type of the water reducer, and a water reducer well known in the art can be used, such as a polycarboxylic acid-based high-efficiency water reducer.
[0038] Based on the mass fraction of the silicate cement, the low-alkali corrosion-resistant composite cementitious system seawater sand concrete provided by the present invention includes 0 to 0.02 parts of retarder, which can be 0 parts, 0.01 parts or 0.02 parts in a specific embodiment. In the present invention, the coagulant is preferably citric acid.
[0039] The present invention provides a method for preparing the low-alkali corrosion-resistant composite cementitious system seawater and sea sand concrete according to the above scheme, comprising the following steps:
[0040] The raw materials are mixed to obtain the low-alkali corrosion-resistant composite cementitious system seawater and sea sand concrete.
[0041] In the present invention, the mixing preferably includes: first mixing silicate cement, ferroaluminate cement, carbonized regenerated micro powder and sea sand, and then adding a mixture of seawater, a water reducer and a retarder to the obtained mixture for second mixing.
[0042] In the present invention, the first mixing and the second mixing are preferably carried out in a mixer; the rotation speed of the first mixing is preferably 140±5r / min. The present invention has no special requirements on the time of the first mixing, as long as the dry materials can be mixed evenly. In an embodiment of the present invention, the time of the first mixing is 3min. In the present invention, the second mixing is preferably first mixed at a rotation speed of 140±5r / min for 3min, and then mixed at a rotation speed of 285±10r / min for 6min.
[0043] After the mixing is completed, the present invention preferably further comprises molding and seawater immersion curing of the obtained mixture in sequence to obtain a molded low-alkali corrosion-resistant composite cementitious system seawater and sea sand concrete.
[0044] In the present invention, the molding preferably includes: pouring the mixture into a mold, vibrating it on a vibration table for 60 seconds, and removing the mold after standing for 24 hours.
[0045] The present invention has no special requirements for the seawater curing, and curing to a specified age is sufficient.
[0046] The low-alkali corrosion-resistant composite cementitious system seawater and sea sand concrete and its preparation method provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0047] The materials used in the following examples and comparative examples are as follows:
[0048] The silicate cement used is PO52.5R cement; the strength grade of ferroaluminate cement is 42.5; the water reducer is a polycarboxylic acid-based high-efficiency water reducer, and the retarder is citric acid; the seawater used is artificially prepared seawater, and the raw materials and proportions of the seawater refer to the specification ASTM D 1141-98; the particle size of the sea sand is 0.08 to 2 mm.
[0049] The preparation method of the carbonized regenerated micropowder is as follows:
[0050] The hardened cement paste was broken into small pieces less than 1 cm in diameter, and then ball-milled in a ball mill at a speed of 600 r / min for 7 minutes (forward rotation for 1 minute, rest for 1 minute, reverse rotation for 1 minute, rest for 1 minute, forward rotation for 1 minute, rest for 1 minute, reverse rotation for 1 minute). The regenerated micro-powder after ball milling was sieved to a particle size less than 0.075 mm. The sieved regenerated micro-powder was spread flat in a carbonization box with a thickness of 1.5 mm, and a carbonization test was carried out for 30 days. The carbonization box setting parameters were 25°C constant temperature, one atmosphere, 70% relative humidity, CO 2 The volume concentration is 20%. The carbonized regenerated micro powder is crushed, ball-milled and sieved to obtain carbonized regenerated micro powder with a particle size of less than 0.075 mm.
[0051] Example 1 and Comparative Examples 1 to 3
[0052] According to the proportions shown in Table 1, silicate cement, ferroaluminate cement, carbonized recycled micro powder and sea sand were dry mixed in a mixer at a slow speed (140±5r / min) for 3min, and then seawater, water reducer and retarder mixture were gradually added, and continued to be stirred at a slow speed (140±5r / min) and a fast speed (285±10r / min) for 3min and 6min respectively. The freshly mixed seawater and sea sand concrete was poured into a cubic mold with a side length of 50mm and vibrated on a vibration table for 60s. After standing for 24h, the mold was removed, and the seawater and sea sand concrete specimens were immersed in seawater at room temperature for curing to the specified age.
[0053] After reaching the specified age, the compressive strength was tested according to the "Test Method for Cement Mortar Strength" GB / T 17671-1999. The pore solution of the specimens at 7 and 28 days of age was squeezed by squeezing the pore solution of concrete, and the pH value of the pore solution was tested using a pH meter. The compressive strength and pore solution test results of the specimens are shown in Table 2.
[0054] Table 1 Raw material dosage of Examples and Comparative Examples
[0055] raw materials Portland cement Ferroaluminate cement Carbonized regenerated powder seawater Sea sand Water reducing agent Retarder Example 1 7 servings 3 servings 2.1 serving 6.05 copies 24.2 servings 0.048 0.018 Comparative Example 1 7 servings 3 servings 0 copies 5 servings 20 servings 0.04 0.015 Comparative Example 2 3 servings 7 servings 0.5 serving 5.25 servings 21 servings 0.042 0.016 Comparative Example 3 3 servings 7 servings 0 copies 5 servings 20 servings 0.04 0.015
[0056] Table 2 Performance data of embodiments and comparative examples
[0057]
[0058] The compressive strength and pH value of Comparative Example 1 were compared with those of Example 1. The results showed that the addition of carbonized regenerated micropowder to the composite cementitious system can significantly improve the 3-day, 7-day and 28-day compressive strength of the seawater and sea sand concrete of the composite cementitious system, and the 28-day compressive strength can reach 72.28MPa. At the same time, due to the volcanic ash effect of the active silica gel in the carbonized regenerated micropowder, the addition of the carbonized regenerated micropowder reduces the pH value of the pore melt of the seawater and sea sand concrete of the composite cementitious system, and the effect of reducing the pH value of the pore melt of the seawater and sea sand concrete at the age of 28 days is more significant, which can be reduced to 11.15, which is friendly to the durability of FRP bars and is suitable for FRP bars to strengthen seawater and sea sand concrete structures.
[0059] Comparing the compressive strength of Comparative Examples 2-3 with that of Example 1, it is found that although Comparative Examples 2-3 have the characteristics of early strength and low alkalinity, the later compressive strength develops slowly, and the 28-day compressive strength is only 38.8% and 39.8% of that of Example 1. This shows that the composite ratio of silicate cement-alumina ferrocement-regenerated micropowder in the composite cementitious system has a significant effect on the compressive strength of seawater sand concrete after hydration and the development of pore solution alkalinity. The performance of the proportion of each component in Example 1 is the most excellent, with lower alkalinity and higher compressive strength after 28 days.
[0060] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A low-alkali corrosion-resistant composite cementitious system seawater and sea sand concrete, comprising the following raw materials in parts by mass: 7 parts of Portland cement, 2-4 parts of ferroaluminate cement, 1.5-2.5 parts of carbonized regenerated micropowder, 20-30 parts of sea sand, 5-7 parts of sea water, 0-0.05 parts of water reducer, and 0-0.02 parts of retarder.
2. The low-alkali corrosion-resistant composite cementitious system seawater and sea sand concrete according to claim 1, characterized in that: The preparation of the carbonized regenerated micropowder comprises: crushing and ball-milling the waste hardened cement slurry in sequence to obtain the regenerated micropowder; and carbonizing the regenerated micropowder to obtain the carbonized regenerated micropowder.
3. The low-alkali corrosion-resistant composite cementitious system seawater and sea sand concrete according to claim 2, characterized in that: The carbonization conditions include: temperature of 20-30° C., relative humidity of 60-80%, air pressure of 1 atmosphere, CO2 volume concentration of 20%, and carbonization time of 15-20 days.
4. The low-alkali corrosion-resistant composite cementitious system seawater and sea sand concrete according to any one of claims 1 to 3, characterized in that: The particle size of the carbonized regenerated micro powder is less than 0.075 mm.
5. The low-alkali corrosion-resistant composite cementitious system seawater and sea sand concrete according to claim 1, characterized in that: The silicate cement includes PO52.5R cement.
6. The low-alkali corrosion-resistant composite cementitious system seawater and sea sand concrete according to claim 1, characterized in that: The strength grade of the ferroaluminate cement is 42.
5.
7. The low-alkali corrosion-resistant composite cementitious system seawater and sea sand concrete according to claim 1, characterized in that: The particle size of the sea sand is 0.08-2 mm.
8. The method for preparing the low-alkali corrosion-resistant composite cementitious system seawater and sea sand concrete according to any one of claims 1 to 7, characterized in that: The following steps are involved: The raw materials are mixed to obtain the low-alkali corrosion-resistant composite cementitious system seawater and sea sand concrete.
9. The preparation method according to claim 8, characterized in that: The mixing comprises: first mixing silicate cement, ferroaluminate cement, carbonized regenerated micro powder and sea sand, and then adding a mixture of seawater, a water reducing agent and a retarder to the obtained mixture for second mixing.
10. The preparation method according to claim 8, characterized in that: After the mixing, the obtained mixture is molded and cured by immersing in seawater in sequence.